Evaluation of upper-limb body postures based on the effects of back and shoulder flexion angles on subjective discomfort ratings, heart rates and muscle activities - Lim, C.-M.; Jung, M.-C.; Kong Y.-K. (Ergonomics, 2011)
A possible limitation of many ergonomics checklists that evaluate postures is an independent evaluation of each body segment without considering the coordination between body segments and resulting in the under-/over-estimation of body postures. A total of 20 men were selected to evaluate the effects of shoulder and back flexion angles on the upper-limb muscle activities, subjective discomforts and heart rates. Interesting findings were obtained from the coordination between back flexion angles and shoulder flexion angles. At a back flexion angle of 45°, the discomfort and heart rates were the least at a shoulder flexion angle of 45°. The %MVC also showed a similar trend. It could be inferred that the 0° shoulder flexion angle would be a natural posture, when the back flexion angle is 0°, whereas 45° shoulder flexion might be a more natural posture when the back flexion angle is 45°.